Analisis Strategi dan Efisiensi Pelayanan Peserta Badan Penyelenggara Jaminan Kesehatan Pada RSU H.Sahudin Kutacane - Muridha Hasan; Sabitah Sabitah (Universitas Veteran Bangun Nusantara, 2023)
This study aims to find out 1. To know the form of service strategy for the Health Insurance Administration Agency at H.Sahudin Kutacane Public Hospital. The population in this study is As for the population in this study are all employees / staff who use BPJS health cards who come to check their health at RSU.H.Sahudin Kutacane. The samples in this study were 134 employees/Medical Officers at the H.Sahudin Kutacane Hospital. The method used in this study is a qualitative method. The nature of this research is classified as descriptive research, namely describing, explaining and interpreting a phenomenon that occurs in an object and the data is qualitative. From the results of the research conducted, it was found that every company without exception at the H. Sahudin Hospital Kutacane has several advantages over the others, on the other hand the company is also inseparable from its weaknesses. The strengths possessed by H. Sahudin Kutacane Hospital are -Service or services provided by H. Sahudin Kutacane Hospital are known for their nice service. Based on the analysis of internal and external factors, the competitive strategy that must be carried out by RSUD H. Sahudin Kutacane in the future is an intensive or integrative strategy.